PENDIDIKAN ISLAM DAN BUDAYA LOKAL: MENAPAKI JEJAK KEARIFAN ISLAM NUSANTARA DALAM TRADISI SAKECO SUMBAWA - Muhammad Thoryq Akbar; Muhammad Muhammad; Muhammad Taisir (FiTUA: Jurnal Studi Islam, 2022)
Sakeco is the art of conveying the message of the ancestral heritage of the Tau Samawa peoples, especially in Desa Beru, Jereweh, Sumbawa Barat. This article aims to reveal the values ​​of Islamic education in the sakeco tradition, and uncover the historical traces of the sakeco tradition. This research uses ethnography research with a qualitative descriptive approach. The data collection method is the method of observation, interviews, and documentation. Methods of data analysis by doing data reduction, display data and draw conclusions. The data validity technique uses observational persistence and source triangulation. The results of this study indicate that Sakeco is the result of the contact of Islam with the local culture of the Tau Samawa peoples. it is used as a means of conveying messages, education, and cultural inheritance. As a local wisdom, the sakeco tradition contains Islamic educational values, including the values ​​of faith education, moral education, and brotherhood education. This tradition is not known for certain when it started, but it is believed to be closely related to the entry and development of Islam in tana Samawa since the 16th century.